EFFECTS OF STUDY STRATEGY AND LEVELS OF FLOW ON RECALL AND RECOGNITION AMONG SECONDARY SCHOOL STUDENTS - Ngala, Collins Ojekeyaeme; Uchegbu, Ifechi Cajethan (African Journal of Social and Behavioural Sciences, 2022)
This study investigated the effect of study strategy and levels of flow on recall and recognition of secondary school student. The study aimed at determining the type of study strategy that ensures a better performance in memory retrieval processes of recall and recognition. This study employed a 4x2 factorial design to investigate effects of study strategy and levels of flow on recall and recognition among eighty students from senior secondary school (SSS) two aged between11-20 years (M = 16.5 years). The participants comprise of 43 males and 37 females. Mefoh’s (2010) ―The Last Search‖ was used as stimulus material while recall and recognition was measured using oral prose assessment test (OPAT) I and II respectively. Wolf study-related inventory was used to measure levels of flow. Multivariate analysis of variance (MANOVA) result revealed significant main effects of study strategy on recall F(3, 5.04) = 90.76, P < .01 but not on recognition. Statistical significant differences existed for participants in both the shallow (F (1, 110.04) = 6.11, P< .05) and intense (F (1, 239.07) = 15.87, P< .01) flow levels in the study. The study affirmed that the reread study method is easier for learners and that the various study strategies investigated do not show the same performance on recall and recognition exercises. As challenges the students’ normal lesson periods was interfered with and the sample used were draw from only a private school. Thus, these researchers recommend that a more controlled study be conducted by first identifying students who study more with a particular method and test them separately. The resultant outcome of the investigation will permit for a stronger comparison and inferences. Also, the replication should be done with public school students on one hand and a mixed sample on another.